(3dHGH GdbhJ ef NRGFf GdedchJs - (3fhQ GdOjf eMehO Hf GdNWjH GdbGTGfj GdMehjs ((3eMehO Hf eMehO Hf Ydi GdMSjfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi cTa Yf Xde GdGYOGe HdeYGf fhQ hLhOg EYde GjgG GdeJYWT Edi PdGd Gdjbjf Gf GdQHhHjI ai XghQgG GYdi eG TgO dg GdYbd hGdfbd s
(3BNQgG (B:s
(3hjchQ Ydjg OhGFQ GdhLhO hddg GdMeO GhdkG hCNQkG hHGWfkG hXGgQkG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1542s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs